Rapid and inexpensive bedside diagnosis of RAN binding protein 2-associated acute necrotizing encephalopathy - Benoît Gouy; Benoît Gouy; Adrien Decorsière; Sophie Desgraupes; Wenming Duan; Hong Ouyang; Yifan E. Wang; E. Ann Yeh; E. Ann Yeh; Alexander F. Palazzo; Theo J. Moraes; Theo J. Moraes; et al. (Frontiers in Neurology, 2023)
Acute necrotizing encephalopathy 1 (ANE1) is a very rare disorder associated with a dominant heterozygous mutation in the RANBP2 (RAN binding protein 2) gene. ANE1 is frequently triggered by a febrile infection and characterized by serious and irreversible neurological damage. Although only a few hundred cases have been reported, mutations in RANBP2 are only partially penetrant and can occur de novo, suggesting that their frequency may be higher in some populations. Genetic diagnosis is a lengthy process, potentially delaying definitive diagnosis. We therefore developed a rapid bedside qPCR-based tool for early diagnosis and screening of ANE1 mutations. Primers were designed to specifically assess RANBP2 and not RGPD (RANBP2 and GCC2 protein domains) and discriminate between wild-type or mutant RANBP2. Nasal epithelial cells were obtained from two individuals with known RANBP2 mutations and two healthy control individuals. RANBP2-specific reverse transcription followed by allele-specific primer qPCR amplification confirmed the specific detection of heterozygously expressed mutant RANBP2 in the ANE1 samples. This study demonstrates that allele-specific qPCR can be used as a rapid and inexpensive diagnostic tool for ANE1 using preexisting equipment at local hospitals. It can also be used to screen non-hospitalized family members and at risk-population to better establish the frequency of non-ANE-associated RANBP2 mutations, as well as possible tissue-dependent expression patterns.Systematic review registrationThe protocol was registered in the international prospective register of systematic reviews (PROSPERO– CRD42023443257).